Death at sea—the true rate of occupational fatality within the Australian commercial fishing industry - Penney, Greg; Byrne, William; Cattani, Marcus (Frontiers in Public Health, 2022)
Although the safety performance of the Australian commercial fishing industry has been the subject of multiple investigations, it has ultimately remained undefined. Whilst most Australian industries notify the Regulator of significant workplace incidents and injuries in their operations, the majority of persons in the commercial fishing industry are contractors who are paid piecework and in some jurisdictions specifically excluded from the worker compensation legislation, meaning that most occupational injuries, including fatalities, are not captured in the centralised workers compensation datasets. This study presents the analysis of a systematic review of industry data-bases, published academic, and, Australian Coroners reports to assist improve the definition of the nation’s commercial fishing industry safety performance. The analysis shows occupational fatality rates are significantly higher than currently reported, and recurring factors contributing to deaths at sea remain unaddressed. The study is significant as it demonstrates how workplace injuries and deaths can be hidden within datasets applying broad industry classification, and provides a foundation for future research in Australian fishing and other industries.